2014
DOI: 10.2217/rme.14.61
|View full text |Cite
|
Sign up to set email alerts
|

Periadventitial Adipose-Derived Stem Cell Treatment Halts Elastase-Induced Abdominal Aortic Aneurysm Progression

Abstract: Aim Demonstrate that periadventitial delivery of adipose-derived mesenchymal stem cells (ADMSCs) slows aneurysm progression in an established murine elastase-perfusion model of abdominal aortic aneurysm (AAA). Materials & methods AAAs were induced in C57BL/6 mice using porcine elastase. During elastase perfusion, a delivery device consisting of a subcutaneous port, tubing and porous scaffold was implanted. Five days after elastase perfusion, 100,000 ADMSCs were delivered through the port to the aorta. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Likely, ASC‐secreted elastin contributed to this normalization, but ASC might also inhibit extracellular elastase. This corroborates studies that postulate that normalization of the elastin integrity is of therapeutic benefit in AAA . The ASC‐loaded patches treated groups also showed that the density of medial SMC was preserved.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Likely, ASC‐secreted elastin contributed to this normalization, but ASC might also inhibit extracellular elastase. This corroborates studies that postulate that normalization of the elastin integrity is of therapeutic benefit in AAA . The ASC‐loaded patches treated groups also showed that the density of medial SMC was preserved.…”
Section: Discussionsupporting
confidence: 89%
“…This is unlikely, because the presence of macrophages was more distal to the media, in particular in comparison to untreated AAAs and those treated with bare patches only. Other studies used intravenous or intramural delivery of stem cells which resulted in poor retention of stem cell . In a porcine model for aneurysm, GFP‐marked bone marrow‐derived were detectable at one week after their injection into the aorta .…”
Section: Discussionmentioning
confidence: 99%
“…The AAA stem cells expressed macrophage surface antigens (CD68), but not VSMC (SM22) or fibroblast (FSP1) markers, and co localized in the aortic wall with the cellular marker of proliferation Ki67. In another study adipose-tissue-derived mesenchymal stem cells were delivered to the aortae of mice induced to have AAA with an elastase treatment [66]. The mice receiving stem cells had smaller AAAs and the elastin fragmentation was less pronounced.…”
Section: Pathophysiology Of Aaamentioning
confidence: 99%
“…Recently, preclinical studies have found mesenchymal stem cell (MSC)-based cellular therapy is beneficial to AAA initiation and progression [14][15][16][17][18][19][20][21]. Parvizi et al [20,21] demonstrated that perivascular scaffolds loaded with adipose-derived MSCs could attenuate AAA development, prevent loss of VSMCs, and decrease macrophage infiltration in rats.…”
Section: Introductionmentioning
confidence: 99%